Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Sections 9.1-9.6 - Integrated Review - Functions and Properties of Logarithms: 3



Work Step by Step

We know that $(f\times g)(x)=f(x)\times g(x)$. Therefore, $(f\times g)(x)=f(x)\times g(x)=(x-6)\times(x^{2}+1)$. We can use the FOIL method to simplify. First= $x\times x^{2}=x^{1+2}=x^{3}$ Outer= $x\times1=x$ Inner= $-6\times x^{2}=-6x^{2}$ Last= $-6\times1=-6$ We can now add these terms together. $x^{3}+x+(-6x^{2})+(-6)=x^{3}-6x^{2}+x-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.